Knowledge Forms and Career Decision Making: A Component of Multidimensional Evaluation - French, Fred; French, Carmel (Canadian Journal of Counselling and Psychotherapy, 2007)
The evaluation of career development programs and services through a multidimensional approach is advocated utilizing adaptations from methodologies found in evaluating cognitive instructional programs. Specifically, the present paper focuses on accessing the various forms of knowledge necessary in career decision-making through introspective, retrospective, and observational procedures. Accessing changes in content knowledge is insufficient in evaluating the effectiveness of career development programs and services. Understanding the strategic, procedural, and self-knowledge of participants is essential in judging outcomes. Initial suggestions for reader comment are provided.